Membrane-Suspended Nanopores in Microchip Arrays for Stochastic Transport Recording and Sensing - Diederichs, Tim; Tampé, Robert (Frontiers in Nanotechnology, 2021)
The transport of nutrients, xenobiotics, and signaling molecules across biological membranes is essential for life. As gatekeepers of cells, membrane proteins and nanopores are key targets in pharmaceutical research and industry. Multiple techniques help in elucidating, utilizing, or mimicking the function of biological membrane-embedded nanodevices. In particular, the use of DNA origami to construct simple nanopores based on the predictable folding of nucleotides provides a promising direction for innovative sensing and sequencing approaches. Knowledge of translocation characteristics is crucial to link structural design with function. Here, we summarize recent developments and compare features of membrane embedded nanopores with solid state analogues. We also describe how their translocation properties are characterized by microchip systems. The recently developed silicon chips, comprising solid state nanopores of 80 nm connecting femtoliter cavities in combination with vesicle spreading and formation of nanopore-suspended membranes, will pave the way to characterize translocation properties of nanopores and membrane proteins in high throughput and at single transporter resolution.